Răspuns :
a + b + c = 226
a + b = 174
a : 2 = b + 12
a = 2 (b + 12)
a = 2b + 24
174 + c = 226
c = 226 - 174
c = 52
2b + 24 + b = 174
3b = 174 - 24
3b = 150
b = 150 : 3
b = 50
a = 174 - 50
a = 124
a + b = 174
a : 2 = b + 12
a = 2 (b + 12)
a = 2b + 24
174 + c = 226
c = 226 - 174
c = 52
2b + 24 + b = 174
3b = 174 - 24
3b = 150
b = 150 : 3
b = 50
a = 174 - 50
a = 124
a+b+c =226
a+b=174
a/2 = 12+b
a+b+c=226
174+ c=226
c= 226-174= 52 - > C=52
a/2 = 12 + b inseamna ca a = 24+2b ->inlocuim in a+b+c-> 24+2b+b+52=226
24+3b+52=226
3b+76=226
3b=226-76
3b=150
B=50
B=50
C=52 Inlocuim si aflam A
a+b+c =226
A+50+52= 226
A= 226 - (50+52)
A=226-102
A=124
a+b=174
a/2 = 12+b
a+b+c=226
174+ c=226
c= 226-174= 52 - > C=52
a/2 = 12 + b inseamna ca a = 24+2b ->inlocuim in a+b+c-> 24+2b+b+52=226
24+3b+52=226
3b+76=226
3b=226-76
3b=150
B=50
B=50
C=52 Inlocuim si aflam A
a+b+c =226
A+50+52= 226
A= 226 - (50+52)
A=226-102
A=124